Selektivitas Pemisahan Isoniazid dan Asetilisoniazid dalam Plasma Manusia In-vitro secara Kromatografi Cair Kinerja Tinggi - Novi Yantih; Yahdiana Harahap; Wahono Sumaryono; Rianto Setiabudy; Lestari Rahayu (Fakultas Farmasi Universitas Pancasila, 2019)
Bioanalysis method is needed to pharmacokinetic study of INH as antituberculosis. The main problem is INH structure is similar to that of acetyl isoniazid (AcINH) as its metabolite. Therefore, a selective separation method is needed to separate the INH from its metabolite and matrix. The aim of this study was to test the selectivity of separation method of INH and AcINH in human plasma in-vitro by high performance liquid chromatography (HPLC). The HPLC system used a reversed phase with UV detector and hexane sulphonate as an ion counter. The optimum conditions was obtained by using C18 as stationary phase, hexane sulphonate (pH 2.47)-methanol (65:35) as mobile phase, with flow rate of 1mL/min, and UV detector at wavelength of 265nm. The selectivity of method separation was indicated by a resolution value of ≥ 1.5. The tailing factor for INH and AcINH were 1.297, dan 1.912, respectively. The k values ware ​​less than 10 and N values ​​were greater than 5000 indicate good separation efficiency. The developing of HPLC was a selective for separating of INH and AcINH in human plasma in-vitro.